2020
DOI: 10.1158/1940-6207.capr-19-0370
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced Norepinephrine Downregulates CCL2 in Macrophages to Suppress Tumor Growth in a Model of Malignant Melanoma

Abstract: ◥Psychological stressors have been implicated in the progression of various tumor types. We investigated a role for stress in tumor immune cell chemotaxis in the B16F10 mouse model of malignant melanoma. We exposed female mice to 6-hour periods of restraint stress (RST) for 7 days, then implanted B16F10 malignant melanoma tumor cells and continued the RST paradigm for 14 additional days. We determined serum corticosterone and liver catecholamine concentrations in these mice. To evaluate the tumor microenvironm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…CCL2 expressed in circulating fibrous cells is involved in the recruitment of Ly6C monocytes and metastasizes B16F10 cells to the lung [119]. In a mouse model, stress-loaded norepinephrine suppresses blood CCL2 levels and macrophage infiltration into cancer tissues, and β-epinephrine receptors may be targets for melanoma treatment [120]. CCR2 inhibitors enhanced the therapeutic effect of anti-PD-1 antibodies in several mouse tumor models [121].…”
Section: Other Cancersmentioning
confidence: 99%
“…CCL2 expressed in circulating fibrous cells is involved in the recruitment of Ly6C monocytes and metastasizes B16F10 cells to the lung [119]. In a mouse model, stress-loaded norepinephrine suppresses blood CCL2 levels and macrophage infiltration into cancer tissues, and β-epinephrine receptors may be targets for melanoma treatment [120]. CCR2 inhibitors enhanced the therapeutic effect of anti-PD-1 antibodies in several mouse tumor models [121].…”
Section: Other Cancersmentioning
confidence: 99%
“…CCL2 is a major chemoattractant implicated in the infiltration of myeloid cells, especially monocytes and neutrophils, into the brain during inflammation 89,90 . A relationship between NE and CCL2 has not been extensively examined in microglia, but a recent report demonstrated that NE reduces CCL2 production in mouse and human macrophages in a β-adrenergic receptor-dependent manner 91 . Additionally, recent work in astrocytes has revealed a complicated relationship between NE and CCL2 that may provide insight for the data in this study and others.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we also screened for the drug candidates of melanoma, and identified corticosterone as a novel therapeutic drug. A recent study showed that stress-induced increase in corticosterone levels suppressed tumor growth in a model of malignant melanoma ( 41 ). It was worth mentioning that the antitumor effect is mainly through reducing recruitment of TAMs ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that stress-induced increase in corticosterone levels suppressed tumor growth in a model of malignant melanoma ( 41 ). It was worth mentioning that the antitumor effect is mainly through reducing recruitment of TAMs ( 41 ). As mentioned above, the infiltration of TAMs is an adverse prognostic factor for melanoma.…”
Section: Discussionmentioning
confidence: 99%